The emergence of Irish gothic fiction : history, origins, theories - Killeen, Jarlath, 1976- (Edinburgh University Press, 2014)
This study provides a robustly theorised and thoroughly historicised account of the beginnings of Irish gothic fiction, maps the theoretical terrain covered by other critics, and puts forward a new history of the emergence of the genre in Ireland.